Marginal adaptation and fracture resistance of virgilite-based occlusal veneers with varying thickness - Amr Rizk; Jylan El-Guindy; Ahmed Abdou; Reem Ashraf; Citra Kusumasari; Farid Emad Eldin (BMC, 2024)
Abstract Statement of problem CAD/CAM occlusal veneers have been developed for minimally invasive prosthetic restoration of eroded teeth. Marginal adaptation and fracture resistance are crucial for the long-term survivability and clinical success of such restorations. Virgilite-based lithium disilicate glass-ceramic is a newly introduced material with claims of high strength. However, constructing occlusal veneers from this material of varying thickness has not been investigated. Purpose The current study aimed to assess the impact of CAD/CAM occlusal veneer thickness and materials on marginal adaptation and fracture resistance. Materials and methods Thirty-two occlusal veneers were constructed and divided into two groups (n = 16) based on the CAD/CAM material into Brilliant Crios and CEREC Tessera. Each group was further subdivided into two subgroups (n = 8) according to the thickness: 0.6 and 0.9 mm. Occlusal veneers were bonded to epoxy resin dies. The marginal gap was evaluated before and after thermodynamic aging. Fracture resistance and failure mode were evaluated for the same samples after aging. Marginal adaptation was analyzed using the Mann-Whitney U test. Fracture resistance was analyzed using Weibull analysis (α = 0.05). Results The marginal gap was significantly increased following thermodynamic aging for tested groups (P < 0.001). CEREC Tessera showed a significantly higher marginal gap than Brilliant Crios before and after aging for both thicknesses (P < 0.05). CEREC Tessera recorded lower significant fracture load values compared to Brilliant Crios (P < 0.05). Conclusions Both CEREC Tessera and Brilliant Crios demonstrated clinically accepted marginal gap values. All groups showed fracture resistance values higher than the average masticatory forces in the premolar region except for 0.6 mm CEREC Tessera. Clinical implications Reinforced composite occlusal veneers demonstrated more favorable outcomes in terms of marginal gap and fracture resistance at both tested thicknesses compared to virgilite-based lithium disilicate glass-ceramic. Additionally, caution should be exercised during the construction of occlusal veneers from virgilite-based lithium disilicate glass-ceramic with reduced thickness.